Combination of Physical Methods and Active Charcoal in Reducing Calcium Oxalate Levels in Kimpul Taro Flour (Xanthosoma sagittifolium) - Noviasari, Santi; Zaidiyah, Zaidiyah; Lubis, Yanti Meldasari (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Abstract: Kimpul Taro tuber is a source of carbohydrates that is widely grown in Indonesia but contains anti-nutritional compounds, namely calcium oxalate. Calcium oxalate can cause itching, irritation, and burning sensation in the mouth, skin, and digestive tract. This study was conducted to determine the effect of the combination of physical methods and activated charcoal on the reduction of calcium oxalate levels in Kimpul taro flour from Aceh Province, Indonesia. The physical method of boiling and steaming with and without the addition of 6% activated charcoal was used in this study. The parameters observed in this study were calcium oxalate content, water content, ash content, crude fiber content, water absorption, and total starch. The results showed that physical treatment can reduce levels of calcium oxalate in Kimpul taro flour. The lowest levels of calcium oxalate were obtained in the boiling method, with calcium oxalate levels of 25.82 mg/100 g. Low oxalate Kimpul taro flour can be used as a local food raw material for food diversification and to reduce the use of wheat flour.Abstrak: Talas Kimpul merupakan sumber karbohidrat yang banyak dibudidayakan di Indonesia, namun mengandung komponen anti nutrisi yang disebut kalsium oksalat. Kalsium oksalat dapat menyebabkan gatal, iritasi, sensasi terbakar pada mulut, kulit, dan saluran pencernaan. Penelitian ini bertujuan untuk menentukan pengaruh kombinasi metode fisik dan arang aktif terhadap penurunan kadar kalsium oksalat pada talas Kimpul di Provinsi Aceh, Indonesia. Metode fisik yang digunakan pada penelitian ini adalah perebusan dan pengukusan dengan dan tanpa penambahan 6% arang aktif. Parameter yang diamati adalah kadar kalsium oksalat, kadar air, kadar abu, kadar serat kasar, daya serap air, dan total pati. Hasil penelitian menunjukkan bahwa perlakuan fisik dapat menurunkan kadar kalsium oksalat pada talas Kimpul. Kadar kalsium oksalat terendah diperoleh pada perlakuan metode perebusan yaitu 25,82 mg/100 g. Tepung talas kimpul rendah oksalat dapat dimanfaatkan sebagai bahan baku pangan lokal untuk diversifikasi pangan dan mengurangi penggunaan tepung terigu.